Antimicrobial Activity and Degradation Ability Study on Nanoparticle-Enriched Formulations Specially Designed for the Neutralization of Real and Simulated Biological and Chemical Warfare Agents - Raluca-Elena Ginghina; Gabriela Toader; Munizer Purica; Adriana-Elena Bratu; Claudiu Lazaroaie; Tudor-Viorel Tiganescu; Ramona-Elena Oncioiu; George-Ovidiu Iorga; Florina-Lucica Zorila; Mihai Constantin; Gabriel Craciun; Florin Comanescu; et al. (MDPI AG, 2022)
The present work reveals a comprehensive decontamination study on real and simulated biological and chemical warfare agents (BCWA). The emphasis was on evaluating the antimicrobial activity against real biological warfare agents, such as Bacillus anthracis, and also the capacity of neutralizing real chemical warfare agents, such as mustard gas or soman, by employing three different types of organic solutions enriched with ZnO, TiO2, and zeolite nanoparticles, specially designed for decontamination applications. The capacity of decontaminating BCWA was evaluated through specific investigation tools, including surface monitoring with the swabs method, minimum inhibitory (MIC) and minimum bactericidal concentration (MBC) evaluations, time-kill tests for microorganisms, and GC-MS for monitoring chemical agents on different types of surfaces (glass, painted metal, rubber, and cotton butyl rubber). These tests revealed high decontamination factors for BCWA even after only 10 min, accomplishing the requirements imposed by NATO standards. At the completion of the decontamination process, the formulations reached 100% efficacy for Bacillus anthracis after 10-15 min, for soman after 20-30 min, and for mustard gas in an interval comprised between 5 and 24 h depending on the type of surface analyzed.